LENNIE SMALL’S SOCIAL INTERACTION IN JOHN STEINBECK’S OF MICE AND MEN - Edinta Tarigan; Ceisy N. Wuntu; Jennie Posumah (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study was to reveal Lennie Small’s social interaction in the novel Of Mice and Men by John Steinbeck. This study was classified as a qualitative research because the writer gathered the data in the form of words as well as quotation from the work itself to support the research. The writer collected the data from two kinds of sources, namely primary source and secondary source. The primary source was taken from the novel Of Mice and Men by John Steinbeck, and the secondary sources are the other material that supports the research such as books, articles, and websites. This study also used a sociological approach to explain the situation that occurred to Lennie Small immigrant worker and how his character development in that time as described in John Steinbeck novel Of Mice and Men. The result of this study showed that there are two kind of social interaction to reveal the main character Lennie Small; associative and dissociative.